Branch, industry, ecosystem: the interrelationship of concepts as applied to tourism - Chaika, Tatiana (Bookmundo, 2024)
The structuring and ordering of scientific knowledge, among other things, inevitably pursues applied goals related to better understanding and facilitating the management of the phenomena or processes under consideration. From this point of view, we approach in this study the problem of interrelation between such concepts as the tourist branch, the tourism industry, the tourism and hospitality ecosystem.
Keywords: tourism; branch; industry; ecosystem; business processes